Chromium incorporated nanocrystalline cobalt ferrite synthesized by combustion method: Effect of fuel and temperature. Issue 16 (November 2017) - Sharma, Suman; Sharma, Narayan Dutt; Choudhary, Nisha; Verma, Mukesh Kumar; Singh, Devinder
Abstract: Nanocrystalline CoCrFeO4 samples were prepared by Cost effective and low temperature combustion method using different fuels as glycine, urea and polyvinyl alcohol and the effect of temperature on their physical properties has been studied. The thermal study of the precursor gels was done by using Thermogravimetric and Differential thermal analysis (TG-DTA). Occurrence of the cubic spinel phase for the samples was confirmed by the Rietveld analysis of X-ray diffraction (XRD) data. The refinement results also confirm that the cationic distribution over the tetrahedral and octahedral sites in the spinel lattice of samples is partially inverse. The magnetic studies indicate a superparamagnetic behaviour, showing an increase in the blocking temperatures with the particle size in case of all fuels. All the samples showed ferromagnetic behaviour and the nanoparticles prepared by using glycine as a fuel were found to have largest crystallite size and relatively stronger A–O–B interaction compared to others. Magnetization measurements exhibit non-collinear ferrimagnetic structure for the samples.